2014
DOI: 10.1038/srep07225
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nano Confinement on the C–H Activation and its Corresponding Structure-Activity Relationship

Abstract: The C–H activation of methane, ethane, and t-butane on inner and outer surfaces of nitrogen-doped carbon nanotube (NCNTs) are investigated using density functional theory. It includes NCNTs with different diameters, different N and O concentrations, and different types (armchair and zigzag). A universal structure-reactivity relationship is proposed to characterize the C–H activation occurring both on the inner and outer surfaces of the nano channel. The C–O bond distance, spin density and charge carried by act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
(203 reference statements)
1
12
0
Order By: Relevance
“…As shown in Figs S5 and S6, *CH 4 dehydrogenation are as follows: *CH 4 → *CH 3 → *CH 2 → *CH → *C, which is in accordance with the previous studies of CH 4 dehydrogenation on different metals and alloys using DFT 31 32 33 34 35 36 37 38 39 . Table S1 shows the adsorption parameters of *CH 4 , *CH 3 , *CH 2 , *CH and *C on a Cu site.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figs S5 and S6, *CH 4 dehydrogenation are as follows: *CH 4 → *CH 3 → *CH 2 → *CH → *C, which is in accordance with the previous studies of CH 4 dehydrogenation on different metals and alloys using DFT 31 32 33 34 35 36 37 38 39 . Table S1 shows the adsorption parameters of *CH 4 , *CH 3 , *CH 2 , *CH and *C on a Cu site.…”
Section: Resultssupporting
confidence: 90%
“…To the best of our knowledge and despite an increasing number of excellent theoretical contributions, the only reported preparative, noncatalyzed, organic chemical reaction performed experimentally within narrow carbon nanotubes is the aromatic halogenation reaction, where it was observed that extreme spatial confinement in narrow single-walled carbon nanotubes (SWNTs) directed the site-selective electrophilic attack of the incarcerated aromatic guest reactant and resulted in an enhancement in the formation of the more linear para-regioisomer from 68 to 97%. In this study, we explore the effect of nanoscale confinement in SWNTs on the formation of the products of 1,3-dipolar cycloaddition reactions, a class of bimolecular reactions with two reactants typically of commensurate size and complexity.…”
Section: Introductionmentioning
confidence: 99%
“…For b-La samples, the position of peak C is intentionally determined by the peak of the sample at 0.5 days of P adsorption in Figure a (132.9 eV), in which we have concluded that this sample is virtually the inner-sphere complexation of HPO 4 2– or H 2 PO 4 – on the surface of La­(OH) 3 particles based on previous results. ,, With respect to La@201, a higher binding energy peak C at 134.7 eV is automatically set by the software to complete the data fitting once the positions of peaks A and B are fixed. The higher binding energy of peak C in La@201 than that in b-La suggests a stronger binding affinity of P species with the La­(OH) 3 crystals under nanoconfinement, where the exposed crystal facets and the chemical environment could be different. , …”
Section: Resultsmentioning
confidence: 99%